Effect of a Novel Adaptive Handle Design on the Ergonomic Performance of Periodontal Curettes in Dental Hygienists with and without Musculoskeletal Disorders: A Pilot Clinical Study - Wink, Cherie; Yang, Susan Meishan; Habib, Ali A.; Lin, Kairong; Takesh, Thair; Wilder-Smith, Petra (Dentistry journal, 2024)
(1) Background: Musculoskeletal disorders (MSDs), discomfort, fatigue, pain, and other acute and chronic work-related injuries are common among dental clinicians. Hand instruments constitute a primary risk factor for these conditions. The overall goal of this study was to compare in dental hygienists with healthy hands, and in those with MSDs, the effect of three different handle designs on instrumentation-related muscle work, comfort, fatigue, and quality of tactile feedback. (2) Methods: Clinicians tested three periodontal curettes: one with a novel adaptive silicone handle, another with a rigid resin handle, and the third with a rigid silicone handle. Ten hygienists—five with MSDs and five without—each scaled three typodonts using the three different curettes. Statistical analysis was performed using a General Linear Model (GLIM) and Tukey’s post hoc test, and a significance level of p < 0.05 was implemented. (3) Results: On average, mean comfort and fatigue across all instruments were significantly worse in testers with MSDs, who also expended significantly more work to complete the same task. In all testers, a novel adaptive handle design was associated with significantly reduced total muscle work and post-instrumentation fatigue, as well as better comfort than conventional rigid handle designs. (4) Conclusions: An adaptive curette handle design demonstrated significantly better ergonomic outcomes than conventional rigid curette handle designs. Hygienists with MSDs expend significantly more muscle work during dental instrumentation.